Answering the Contemplative Call: First Steps on the Mystical Path. - McColman, Carl (Broadleaf Books, 2021)
In Answering the Contemplative Call, Carl McColman shows readers how to apply the riches of the mystical tradition to daily living. Quoting the great mystics of the Christian tradition who have also traveled this path, McColman offers a practice that will help readers come to a place meaning and purpose in their lives.
Keywords: Religion.; Mysticism.; Contemplation.; Mysticisme.; religion (discipline); mysticism.; Religion; Contemplation; Mysticism